The Validation of the Military and Veteran Family Cultural Competency Model (MVF-CCM). (2nd January 2020) - Tam-Seto, Linna; Krupa, Terry; Stuart, Heather; Lingley-Pottie, Patricia; Aiken, Alice; Cramm, Heidi
Abstract: There is increasing use of cultural competency models to guide health care interactions with military community members, including families, however, at this time there is no validated model. This study confirms the accuracy of the Military and Veteran Family Cultural Competency Model (MVF-CCM). Using a systems theory-informed qualitative approach, focus groups and interviews were conducted. Data were analyzed using a step-wise process to integrate changes. Feedback was provided to both the model and framework to expand on content and increase clarity. The MVF-CCM is an evidence-informed resource to support the development of cultural competent health care curriculum, continuing education opportunities, and clinical practice.